Polymer-Based Mass Cytometry Reagents: Synthesis and Biomedical Applications - Yin-Feng Wang; Wenying Wu; Ya-Hui Ge (Molecules)
Mass cytometry has promoted the development of single-cell analysis by enabling the highly multiplexed detection of cellular markers using metal-tagged antibodies or cells. Polymer-based mass cytometry reagents have played a critical role in this technique due to their structural versatility, high metal-loading capacity, and sensitivity. This review comprehensively examines the advances in polymer-based reagents for mass cytometry, focusing on their design principles, synthetic strategies, and biomedical applications. We systematically analyze three key categories: metal-chelating polymers with macrocyclic/acyclic chelators developed through controlled polymerization techniques, polymeric particles including encoded microspheres and semiconducting polymer dots, and emerging metal–organic frameworks with high metal-loading capacities. The discussion highlights how these engineered materials overcome spectral limitations of conventional flow cytometry while addressing current challenges in sensitivity, and multiplexing capacity. Finally, we outline current challenges and future research directions for developing polymer probes in single-cell mass cytometry.